Social and economic benefits of cashew (Anacardium occidentale) cultivation in Dakshina Kannada, Karnataka: An analysis of the impact, its determinants and constraints - SAJEEV, M V; SAROJ, P L (The Indian Journal of Agricultural Sciences, 2015)
The study measured social and economic benefits accrued from cashew (Anacardium occidentale L.) cultivation in relation with constraints faced by cashew farmers in the Dakshina Kannada district of Karnataka. An ‘ex-post-facto cause to effect’ design was used and findings indicated that most cashew farmers derived moderate socio-economic benefits particularly with high social benefits in comparison to low economic benefits. High levels of social participation, extension participation, mass media exposure and opinion leadership were measured among majority of the farmers practicing cashew cultivation. Impact on cropping pattern, labour engagement and farm expenditure were found to be low while increase in family incomes and expenditure were reported. The regression analysis revealed that four personal variables, viz. the age of cashew farmer, years of experience in farming, cosmopoliteness and distance of cashew plot from home and one economic variable, i.e. importance given to cashew cultivation as exerting a significant positive contribution towards explaining the variability in socio-economic impact. The variables used in the study could together explain up to 67% variability in socio-economic impact. The stepwise regression model developed to predict socio-economic impact explained up to 68% of the variation in socioeconomic impact using the predictors; importance given to cashew (X1), years of experience in farming (X2), cosmopoliteness (X3), distance of cashew plot from home (X4), extension participation (X5), land used for other crops (X6) and net income from cashew farming (X7). The study revealed major constraints faced by farmers like poor price quoted by traders and the price fluctuations for raw cashew nut, scarcity of of hired labourers, incidence of tea mosquito bug owing to crop loss and death of yielding trees due to cashew stem and root borer attack.